Development of a mechanistic model for analyzing avian reproduction data for pesticide risk assessment. (15th June 2023) - Trijau, Marie; Goussen, Benoit; Brain, Richard; Maul, Jonathan; Galic, Nika
Abstract: Mechanistic effect models are increasingly recommended as tools for refining evaluations of risk from exposure to pesticides. In the context of bird and mammal risk assessments, DEB-TKTD models have been recommended for characterizing sublethal effects at lower tiers. However, there are currently no such models. Currently, chronic, multi-generational studies are performed to characterize potential effects of pesticides on avian reproduction, but it is has not been established to what extent results from these studies can inform effect models. Here, a standard Dynamic Energy Budget (DEB) model was extended to account for the avian toxicity endpoints observed in regulatory studies. We linked this new implementation to a toxicological module to capture observed pesticide effects on reproduction via a decreased efficiency of egg production. We analysed ten reproduction studies with five different pesticides conducted with the mallard ( Anas platyrhynchos ) and the northern bobwhite ( Colinus virginianus ). The new model implementation accurately distinguished between effects on egg production from direct mechanism of toxicity and from food avoidance. Due to the specific nature of regulatory studies, model applicability for risk refinement is currently limited. We provide suggestions for next steps in model development. Graphical abstract: Image 1 Highlights: DEB-TKTD models are recommended for assessment of sublethal effects on birds. Here we propose such a model to analyse effects on growth and reproduction. Five pesticides were tested using the mallard duck and the bobwhite quail. The model accurately distinguished between direct toxic and food avoidance effects. Abstract : Synopsis: Pesticide risk assessment for birds lacks a mechanistic framework for analysing avian reproduction study data. Our study presents a bioenergetics model for integrating biological endpoints measured in these studies and predicting pesticide effects on bird reproduction.